Modeling of different scenarios for the spreadof COVID-19 by using the cellular automata - Kosovych, Ihor; Cherevko, Ihor; Vyklyuk, Yaroslav; Nevinskyi, Denys (IEEE, 2022)
n this research, we used the method of mobile cellular automata to study the dynamics of COVID-19. A number of simulation scenarios that take into account different quarantine restrictions are considered and compared. The simulation results revealed that self-isolation regimen is the most effective way to reduce the rate of infection. The simulation model that was developed in the work allows you to easily adapt and take into account new factors of quarantine restrictions.
Keywords: COVID-19 , Adaptation models , Epidemics , Analytical models , Infectious diseases , Computational modeling , Simulation